Interest differences and organizational learning - Laurie Field (Administrative Sciences, 2017)
This paper argues that interest differences are the key to understanding the nature of organizational learning and the processes by which it occurs, yet the concept of 'interest' is very much underdeveloped in the organizational learning literature. Drawing on the work of Habermas and Lukes, the paper proposes a model of the relationship between shared learning and interests and elaborates on it using a case study of pay and performance management change at a large Australian finance-sector company, DollarCo. The case study provides many examples of shared learning associated with both common and competing interests, including a great deal of learning resulting from tensions between DollarCo's economic and technical interests, on the one hand, and employees' ontological interests on the other. By doing so, it underlines the value of foregrounding interests and interest differences in studies of workplace and organizational learning and raises questions about the extent to which many published accounts of so-called 'organizational' learning are actually describing 'shared interest group' learning.
Keywords: 350; interests; organizational learning; power; workplace learning